Where the wild things are - Sendak, Maurice ([New York] : HarperCollins, 1984)
After he is sent to bed without supper for behaving like a wild thing, Max dreams of a voyage to the island where the wild things are.
Caldecott Medal/Honor.
Elem. School Library Collection.
Wilson's Children.
Book Links (A.L.A.), July 2006.
Child Study Children's Book Committee, June 2002.
Christian Library Journal starred, June 2007.
Keywords: Dreams -- Fiction; Dreams -- Fiction